Secure Big Data Access Control Policies for Cloud Computing Environment (International Journal of Innovative Research in Computer Science & Technology, 2024)
As the term indicates the Big data it means  we are work for the something big or can say something  large in the Amount, Data the high volume is known as  the big data.Now a Day for storing the data file in the  Computer Science Engineering we are used the Hard  disk, some of the storage place , these storage device  may store the data in a Giga byte capability and  Terabyte capability or many more, Now a day we are  used the some new technology call the cloud  environment. So in this work I am study the big data  storing process in the Cloud environment, big data  fetching from the cloud in a securer manner. So in this  dissertation work I am also include the some  information about the existing work and some of the  algorithm that war already proposed by the researcher  in the various paper. My work is based on the  Attribute-Based Encryption(ABE) is promising  technique to ensure the end-to-end security of big data  in the cloud However, the policy updating has always  been a challenging issue when ABE is used to construct  access control schemes.
Keywords: ABE; Big Data; cloud; Cipher; Plain Text